Are BRCA1 and BRCA2 gene mutation patients underscreened for pancreatic adenocarcinoma?. Issue 6 (12th January 2019) - Roch, Alexandra M.; Schneider, Justine; Carr, Rosalie A.; Lancaster, William P.; House, Michael G.; Zyromski, Nicholas J.; Nakeeb, Attila; Schmidt, C. Max; Ceppa, Eugene P.
Abstract : Background: Breast cancer (BRCA) mutations account for the highest proportion of hereditary causes of pancreatic ductal adenocarcinoma (PDAC). Screening is currently recommended only for patients with one first‐degree relative or two family members with PDAC. We hypothesized that screening all BRCA1/2 patients would identify a higher rate of pancreatic abnormalities. Methods: All BRCA1/2 patients at a single academic center were retrospectively reviewed (2005‐2015). Pancreatic abnormalities were defined on cross‐sectional imaging as pancreatic neoplasm (cystic/solid) or main‐duct dilation. Results: Two hundred and four patients were identified with BRCA mutations. Forty‐seven (40%) had abdominal imaging (20 computerized tomography and 27 magnetic resonance imaging). Twenty‐one percent had pancreatic abnormalities (PDAC [n = 2] and intraductal papillary mucinous neoplasm [IPMN; n = 8]). The prevalence of pancreatic abnormalities and IPMN was higher in BRCA2 patients than in the general population (21% vs 8% and 17% vs 1%; P = 0.0007 and P < 0.0001, respectively), with no influence of family history. Similarly, BRCA1 patients had an increased prevalence of IPMN (8.3% vs 1%; P < 0.0001). Conclusions: In this series, 4% and 17% of BRCA2 patients developed PDAC and IPMN, respectively. Eight percent of BRCA1 patients developed IPMN. Under current recommended screening, 60% of BRCA1/2 patients had incompletely pancreatic assessment. With no influence of family history, this study suggests all BRCA1/2 patients should undergo a high‐risk screening protocol that will identify a higher rate of precancerous pancreatic neoplasms amenable to curative resection.